The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1111/j.1348-0421.2000.tb02481.x
|View full text |Cite
|
Sign up to set email alerts
|

An Exfoliative Toxin A‐Converting Phage Isolated from Staphylococcus aureus Strain ZM

Abstract: Exfoliative toxin A (ETA) causes staphylococcal scalded-skin syndrome in children. The gene for ETA was believed to be coded by the chromosomal DNA. We isolated temperate phages from an ETA-producing strain, ZM, using a restriction minus strain, 1039, as an indicator. One of the prophages, designated revealed that phage (1)-ZM-1 carries the structural gene for ETA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Genomic analyses revealed that the ETA gene is chromosomally located, whereas the ETB gene is carried on plasmids [8,10]. Furthermore, the eta gene is encoded in the genomic sequence of a temperate phage, and phage infection converts ETA non-producing strains into ETA producers [11,12]. ETA and ETB comprise 242 and 246 amino acids, respectively, and share approximately 40% amino acid homology [8].…”
Section: Exfoliative Toxins Resembling Trypsin-like Serine Proteases mentioning
confidence: 98%
“…Genomic analyses revealed that the ETA gene is chromosomally located, whereas the ETB gene is carried on plasmids [8,10]. Furthermore, the eta gene is encoded in the genomic sequence of a temperate phage, and phage infection converts ETA non-producing strains into ETA producers [11,12]. ETA and ETB comprise 242 and 246 amino acids, respectively, and share approximately 40% amino acid homology [8].…”
Section: Exfoliative Toxins Resembling Trypsin-like Serine Proteases mentioning
confidence: 98%
“…Three distinct ETs, ETA, ETB, and ETD, which are proteins of 27-30 kDa, have been identified in S. aureus. The genes for these ETs, eta, etb, and etd, have been identified on mobile genetic elements, e.g., a bacteriophage for eta, a plasmid for etb, and a pathogenicity island for etd, indicating that S. aureus strains might have increased or changed their pathogenic potential by acquiring virulent determinants [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Yoshizawa et al [31] described, for the first time, a temperate phage that carried the structural gene for ETA from an ETA-producing strain of S. aureus. Yamaguchi et al [32] also isolated a phage (φ ETA) that encodes an ETA from S. aureus, isolated from a human impetigo patient, and determined the complete nucleotide sequence of the φ ETA genome.…”
Section: Discussionmentioning
confidence: 99%